Phytochemical analysis of some plant latex - Manoorkar VB; Gachande BD (International Journal of Life Sciences, 2015)
Phytochemical analysis of plant latex was carried out from ten plant species from Nanded region for presence of secondary metabolites such as alkaloids, flavonoids, phenols, tannin, saponin, terpenoids, steroids and glycosides. Alkaloids were found in all plant latex except F. benghalensis & C. papaya, while flavonoids and phenols revealed the presence in all latex samples except Nerium oleander & Carica papaya. Calotropis procera, Jatropa curcas, J. gossypifolia, N. oleander, C. papaya showed presence of Saponin but absence of tannins. Terpenoids are absent in Euphorbia tirucalli, Ficus benghalensis, F. religiosa. Steroids are present in E. tirucalli, C. procera, F. benghalensis, while glycosides were absent in E. tirucalli, N .oleander and F. religiosa.